A new rheophytic species of Carissa (Apocynaceae) from Northeast India - Jatindra Sarma; Hussain A. Barbhuiya; Santanu Dey (Journal of Asia-Pacific Biodiversity, 2020)
A new species, Carissa kopilii, is described and illustrated from Northeast India. The taxonomic relationships of the new species with closely allied species of genus Carissa are examined and discussed.